The contradictions in the existing physics and the psychological factors that influence them to be valued - Tu, Runsheng (International Journal of Scientific Reports, 2020)
Besides the limitation of cognition level, the factors that affect the correctness of academic evaluation are as follows: collusion-recognization effect, backfire effect, cognitive maladjustment, inattentional blindness and aesthetic fatigue. It’s hard for readers (especially the reviewers of academic achievements) not to fall into the trap. Therefore, the probability of misjudgment of academic achievements of "questioning and denying current prevailing theories or creating new theories" is very high. The intolerable contradictions in the existing physical theories, such as space paradox, time paradox, quantum entanglement paradox, are exposed by means of thought experiments and "to present the facts, reason things out", and take these works as examples to reveal the formation and utilization of these adverse psychological effects. The conclusions are as follows: both special relativity and Copenhagen interpretation of quantum mechanics have fatal injury; it is difficult to eliminate the misjudgment of academic achievements, but the misjudgment rate can be reduced. The concepts of “invariance of spatial attribution” and “inaction association” are established. These works can urge readers to treat new and old physics theories more carefully, promote the development of physics, and promote the birth and improvement of the evaluation theory of science and technology.